Micro-nozzle flow and thrust prediction with high-density ratio using DSMC selection limiter - Frieler, T.; Groll, R. (Frontiers in Space Technologies, 2023)
A DSMC solver with a modified collisional routine is used to investigate an argon gas flow through a millimetre-scaled arcjet thruster nozzle with high density ratios. The limiter scheme, here denoted as Constant Selection Limiter (CSL), limits the possible number of selected collisional pairs to a constant value, in accordance to the present simulation particles in the cell. Results of the CSL scheme are compared to both experimental results and numerical results of a compressible Navier-Stokes solver, as well as discussed in comparison to baseline DSMC simulations. The influence of collision limitation by the CSL is discussed on the stagnation pressure of the thruster and on thrust and specific impulse prediction. Applying the limiter scheme, prediction of the stagnation pressure becomes challenging in some cases. In contrast, thrust and specific impulse are predicted well and their study remains valid. Investigated mass flow rates are between 0.178mg/s ≤ m˙ ≤ 71.360mg/s and flow Knudsen numbers below Kn = 0.01 and over Kn = 10 are present. Near atmospheric conditions are reached inside the thruster, generating pressure ratios up to 3741 along the nozzle. The computational performance of the scheme is also discussed and speed-up factors up to 0.51 are achieved.